Etternamnsbruk i Luster kommune i to hundre år - Mascetti, Samuele (NAMN OG NEMNE, 2020)
This article discusses the evolution of surnames in Luster municipality, which until 1963 was divided into three smaller, separate districts (Hafslo, Jostedal, and Luster itself). The aim is to investigate surname usage in the period that both preceded and followed the official name law from 1923, based on a quantitative analysis of the censuses from 1801 and 1900, the national farm register from 1950, and the telephone directory from 1979-80. The results show that as the name law took effect, surnames in Luster developed from renaming-based primary patronymics to place name-based hereditary surnames or secondary patronymics, thus corresponding to Norway’s average development. Nevertheless, about 80 % of the locals in Jostedal bore place name-based surnames already in 1900. The article argues that the small and socially homogeneous population of Jostedal was never particularly affected by the hereditary surname tradition from the old Danish upper class, and therefore transitioned from primary patronymics to modern surnames earlier and more freely than the more stratified communities of Hafslo and Luster.